P187 Matrix metalloproteinases and their inhibitors in sputum of asthmatics. (14th November 2013) - Sankaran, P; Jupp, O; Jefferson, M; Sexton, D; Brockwell, C; Clark, I; Wilson, AM
Abstract : Introduction and Objectives: Metalloproteinases are implicated in the development of airway remodelling in asthma due to their ability to cleave collagen and elastin with extracellular matrix. We optimised a method to purify messenger Ribonucleic acid (mRNA) sputum samples. Methods: The mRNA expression of a wide range of pertinent Matrix Metalloproteinases (MMP), A Disintegrin And Metalloproteinases (ADAM), A Disintegrin And Metalloproteinase with Thrombospondin Motifs (ADAMTS) and Tissue Inhibitors of Metalloproteinases (TIMP) was measured from induced sputum with hypertonic saline using Quantitative Real Time Polymerase Chain Reaction (qRT-PCR) in 17 (11 male) non-smoking adults with steroid naive asthma and 12 (6 male) healthy controls. Ten patients with asthma completed open labelled montelukast therapy 10mg per day for 8 weeks. Total mRNA was extracted from the cellular content of the induced sputum plug using a combination of Trizol extraction and Qiagen RNeasy spin columns. To each 0.5ml Trizol extract, 300µl of chloroform was added. The aqueous layer was recovered into a fresh tube and mixed with a half volume of 100% ethanol. Samples were applied to RNeasy Mini spin columns. RT-PCR, using Taqman low-density arrays, was used to determine gene expression. Results: The mean (SD) age and forced expiratory volume in 1 second of asthmatics was 36 (13.4) years and 101.16 (15.47)% predicted respectively and for healthy volunteers was 36 (7.2) years and 92.16 (17.43)% predicted. MMP25 expression was significantly (p = 0.04) higher and MMP15 expression was significantly (p = 0.04) lower is asthmatics compared to healthy volunteers. ADAM28 was significantly (p = 0.03) higher and ADAM17 and ADAMTS15 expression were significantly lower in asthma (p = 0.007 & 0.008 respectively). TIMP2 expression was significantly (p = 0.007) lower in the asthma. There were no significant changes in expression of any of the metalloproteinases or their inhibitors after montelukast therapy. Conclusion: We have studied a wide range of known MMPs, ADAMs, ADAMTSs and inhibitors with a refined technique and successfully increased the yield from induced sputum samples. Significant differences were found between healthy volunteers and asthmatic patients for gene expression of some metalloproteinases/TIMPs. This technique could be used in the future when evaluating gene expression in asthma.